Pelatihan Legalitas dan Kemasan Produk pada Kelompok Usaha Mikro (KUM) Salai Sedap - Hermawati, Lisa; Indriani, Santi; Sari, Enda Kartika (Yumary: Jurnal Pengabdian kepada Masyarakat, 2025)
Purpose: To strengthen the capacity and competitiveness of the Salai Sedap microenterprise group (KUM) in Ogan Komering Ulu, South Sumatra, by improving participants' understanding of business legality (registration and simple permit management) and their skills in designing market-appropriate product packaging. Methodology/approach: Community-based training was conducted in Ogan Komering Ulu for Salai Sedap KUM using intensive workshops and hands-on practice. The activities included interactive learning sessions, expert presentations from relevant agencies and packaging designers, case studies, and prototype packaging exercises. Results/findings: Participants showed a significant increase in knowledge of legal requirements and packaging design skills. Many completed basic legal documentation and developed new market-ready packaging prototypes. Feedback was positive, and participants expressed a strong commitment to implementing changes, with expected improvements in sales and business sustainability. Conclusion: The training effectively enhanced the participants' legal knowledge and packaging skills, which are crucial for their business growth. The positive outcomes suggest that similar training programs can be beneficial for other microenterprise groups, fostering a supportive environment for sustainable economic development. Limitations: The study was limited to one community group in one district, with a short follow-up period; therefore, long-term impacts and wider generalizability remain unconfirmed. Contribution: This study provides a practical model for capacity-building interventions that combine legal literacy and packaging design for microenterprises. It is useful for practitioners, local governments, community development programs, and researchers in small business development and rural economic empowerment.